Changes in invasive pneumococcal disease among adults living with HIV following introduction of 13-valent pneumococcal conjugate vaccine, 2008–2014. (4th October 2017) - Kobayashi, Miwako; Adih, William; Li, Jianmin; Gierke, Ryan; Almendares, Olivia M; Watt, James; Alden, Nisha; Petit, Susan; Farley, Monica; Harrison, Lee; Lynfield, Ruth; Baumbach, Joan; et al.
Abstract: Background: People living with HIV (PLHIV) are at increased risk of invasive pneumococcal disease (IPD). Introduction of 13-valent pneumococcal conjugate vaccine (PCV13) in children in 2010 reduced adult IPD burden (indirect effects). In 2012, PCV13 was recommended in series with 23-valent polysaccharide vaccine (PPSV23) for adults with immunocompromising conditions, including PLHIV. We evaluated changes in IPD incidence in adults ≥19 years old with and without HIV after PCV13 introduction for children in 2010 and for immunocompromised adults in 2012. PCV13 coverage for adults 19–64 years old with indications was 6% in 2014. Methods: IPD cases, defined as pneumococcal isolation from sterile sites, were identified through CDC's Active Bacterial Core surveillance, with counts projected nationally. HIV status was obtained from medical records. Isolates were serotyped by Quellung reaction or PCR and grouped into PCV13-types, PPV11-types (unique to PPSV23), or non-vaccine types. We estimated IPD incidence (cases per 100, 000 people) using national case-based HIV surveillance (for PLHIV) or US Census data (for non-PLHIV) as denominators. We compared IPD incidence in 2011–12 and 2013–14 to the pre-PCV13 baseline (2008–09) by serotype groups. Results: Overall IPD incidence at baseline was 354.0 for PLHIV and 15.5 for non-PLHIV. From baseline to 2013–14, IPD rates declined in both PLHIV (-36.3%; 95% CI: -38.8, -33.7%) and non-PLHIV (-27.3%; 95% CI: -28.2, -26.5%). The largest reductions were noted in PCV13-type IPD in both PLHIV (Figure 1) and non-PLHIV (Figure 2) for both periods (-46.8% for PLHIV and -45.9% for non-PLHIV in 2011–12; -60.3% for PLHIV and -65.8% for non-PLHIV in 2013–14). Overall IPD rates were 22.8 (95% CI: 22.2, 23.4) times as high in PLHIV compared with non-PLHIV at baseline, and 19.4 (95% CI: 18.8, 20.0) times as high in 2013–2014. Conclusion: IPD rates declined significantly in both PLHIV and non-PLHIV during the study period due to reductions in PCV13-type IPD; however, IPD rates remained 20-fold in PLHIV compared with non-PLHIV. Similar magnitude reductions in PCV13-type IPD in both groups and low PCV13 coverage in immunocompromised adults suggest that most of the observed decline is due to PCV13 indirect effects from childhood immunization. Disclosures: L. Harrison, GSK: Scientific Advisor, Consulting fee; W. Schaffner, Pfizer: Scientific Advisor, Consulting fee; Merck: Scientific Advisor, Consulting fee; Novavax: Consultant, Consulting fee; Dynavax: Consultant, Consulting fee; Sanofi-pasteur: Consultant, Consulting fee; GSK: Consultant, Consulting fee; Seqirus: Consultant, Consulting fee